Investigation of Hybrid Silicon-Nitride/Polymer Waveguides for Second-Harmonic Generation - Subrata Das; Brett R. Wenner; Jeffery W. Allen; Monica S. Allen; Michael Vasilyev (IEEE Photonics Journal, 2019)
We propose a hybrid silicon-nitride (Si3N4 or SiN for short)/nonlinear polymer waveguide to achieve second-harmonic generation of an input 1550 nm signal by modal phase-matching between zero-order spatial mode at 1550 nm and second-order mode at 775 nm. We explore and optimize two cases, single channel waveguide and slot waveguide, by varying the waveguide dimensions. For TE polarized light, the optimum slot waveguide exhibits an effective interaction area Aeff of about 16 μm2, which is an order-of-magnitude improvement over the single channel waveguide and can translate to a high value of effective nonlinearity. We also show that the optimum slot waveguide geometry is robust with respect to fabrication uncertainties and bending effects.